Articulate Storyline 3 multimedia based on gamification to improve critical thinking skills and self-regulated learning - Leny Heliawati; Linda Lidiawati; Indarini Dwi Pursitasari (Institute of Advanced Engineering and Science, 2022)
This study measured the effectiveness of Gamification-based Articulate Storyline 3 multimedia on students' critical thinking skills and self-regulated learning. The research method used is a quasi-experimental method. The research subjects were 64 students and eight science teachers who have used the Gamification-based Articulate Storyline 3 multimedia on the nature of acidic, alkaline, and neutral solutions. Data collection techniques in this study were tests that aim to determine students' critical thinking skills and a questionnaire to measure students' learning independence. The data analysis technique was based on calculating the average score of the test items with high-order thinking skills and student learning independence. The study results obtained an average score of 81.50 for critical thinking skills on the material concept of the nature of the acid, base, and neutral solutions with an N-Gain of 72% in the high category. It was also known that the average percentage of student learning independence was 86.76% which falls into the good category. Therefore, Gamification-based Articulate Storyline 3 multimedia can improve students' critical thinking skills and independent learning on the nature of the acid, base, and neutral solutions.